Mechanism of phase separation in a weakly interacting system with strong dynamic asymmetry. Issue 28 (16th March 2017) - Chandran, C. Sarath; Antolasic, Frank; Shanks, Robert A.; Thomas, Sabu
ABSTRACT: We investigated the dynamics of phase separation in a bisphenol A diglycidyl ether (BADGE)–poly(trimethylene terephthalate) (PTT) blend in this study, along with its effects on the long‐term mechanical properties of the blend. BADGE–PTT blends with 4, 4′‐diaminodiphenyl sulfone were prepared by a conventional melt‐mixing technique followed by curing at 180 °C for 4 h. PTT is a rapidly crystallizing polymer because of its unique stereochemistry. The crystalline fraction of PTT is incompatible with BADGE, whereas the amorphous fractions are miscible. Similarly, the blend of BADGE and PTT represented a system with a strong dynamic asymmetry. We examined the effect of the curing (crosslinking) of BADGE in the system discussed previously, with a special emphasis on the viscoelastic properties and long‐term mechanical properties because they are extremely important in tuning these materials for various high‐performance applications in the aerospace industry. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45059. Abstract :